2017
DOI: 10.7754/clin.lab.2016.160912
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR Detection of the Most Common Bacteria and Viruses Causing Meningitis

Abstract: Early diagnosis and treatment of meningitis are very important for reducing its mortality and morbidity. In patients with suspected meningitis, early detection of the responsible agents may be possible with molecular methods, such as PCR. Significant economic benefits may be obtained by preventing unnecessary antibiotic use and hospitalizations through the early detection of the microbial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
2
5
1
Order By: Relevance
“…Of the DNA viruses that cause CNS infection, the varicella zoster virus is common. This finding differs from previous reports [ 16 ], but it is consistent with domestic reports [ 17 ]. The frequency of varicella zoster virus cases may be related to the area from which the patients were sampled, but these findings require further validation.…”
Section: Discussionsupporting
confidence: 78%
“…Of the DNA viruses that cause CNS infection, the varicella zoster virus is common. This finding differs from previous reports [ 16 ], but it is consistent with domestic reports [ 17 ]. The frequency of varicella zoster virus cases may be related to the area from which the patients were sampled, but these findings require further validation.…”
Section: Discussionsupporting
confidence: 78%
“…However, Akkaya et al, (2017) demonstrated that Enterovirus was the most frequently identified agent followed by Adenovirus and S . pneumoniae [ 36 ]. The discrepancy in the causative agents among different studies may be due to different age groups and different geographical area.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the study include the application of the technique exclusively in monomicrobial cultures, the slowness and less sensitivity compared with molecular methods [21,22], and the possibility of bringing out contaminants that are further recovered in the liquid cultures, as negative-coagulase staphylococci. We informed clinicians responsible for the respective patients of any isolates recovered exclusively in the liquid media, although in the case of negative-coagulase staphylococci we advised evaluation with caution in terms of the significance of the microorganism in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%